PARTISIPASI PEREMPUAN DALAM PEMBANGUNAN INFRASTRUKTUR JALAN PERTANIAN DI DESA WATULANEY TIMU KECAMATAN LEMBEAN TIMUR KABUPATEN MINAHASA - Ribka ., Mangimbulur; Melsje Yellie Memah; Elsje Pauline Manginsela (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine how much women's participation in the construction of agricultural road infrastructure. This research was conducted in Watulaney Village, East Lembean, Minahasa Regency and lasted for 3 months, from October to December 2018. Methods of data collection in this study used primary data collected through interviews based on a list of questions, using Likert Scale, that had been prepared previously. Secondarydata obtained from the Office of the Village Watulaney Timu, local book stores, and internet throught google scholar to get article from journals and thesis from others university that related to this research topic . Dataanalysis using qualitative and quantitative descriptive analysis, where this method describes each data taken from women's participation and then presented in table form. For the measurement of women's participation using a Likert Scale. The research results showed that the level of women's participation in agricultural road infrastructure development programs was classified as very active in providing participation in the form of thoughts, energy, skills and assets and objects at the planning, implementation and evaluation stages. With a total score of 426 or 71%, it can be said to be classified as very active.*eprm*